2018
DOI: 10.1093/ofid/ofy241
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Nonsusceptible Gram-Negative Pathogens in ICU and Non-ICU Settings in US Hospitals in 2017: A Multicenter Study

Abstract: BackgroundInfections caused by Gram-negative pathogens resistant to carbapenems have limited treatment options and are associated with increased morbidity and mortality. We evaluated the rates, infection sources, and pathogen types associated with carbapenem-nonsusceptible (Carb-NS) Gram-negative isolates in intensive care unit (ICU) and non-ICU settings in a large US hospital database.MethodsWe conducted a retrospective cross-sectional analysis of carbapenem susceptibility of all nonduplicate isolates of Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 28 publications
5
56
2
3
Order By: Relevance
“…NHSN Acinetobacter resistance rates for HAIs were also higher: 49.5% of tested Acinetobacter isolates were Carb-NS in 2014 data (Anon, 2015a) compared with 34.4% estimated here for inpatients. Consistent with these data, McCann et al observed a higher proportion of Carb-NS Gram-negative isolates in hospital-onset (6.8%) versus admission (2.4%) cultures in the BD Insights database (McCann et al, 2018).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…NHSN Acinetobacter resistance rates for HAIs were also higher: 49.5% of tested Acinetobacter isolates were Carb-NS in 2014 data (Anon, 2015a) compared with 34.4% estimated here for inpatients. Consistent with these data, McCann et al observed a higher proportion of Carb-NS Gram-negative isolates in hospital-onset (6.8%) versus admission (2.4%) cultures in the BD Insights database (McCann et al, 2018).…”
Section: Discussionmentioning
confidence: 59%
“…Based on our data, isolates of the most common antibiotic-resistant phenotype in our study, ESBL Enterobacteriaceae, are present in 1 of every 141 inpatients. We have previously shown that a given isolate in our database may have multiple antibiotic-resistant phenotypes (for instance, Carb NS Enterobacteriaceae could potentially also be MDR) (McCann et al, 2018), so it is not appropriate to add inpatient rates from different resistance phenotypes to estimate an overall burden. Nevertheless, the ESBL figure alone indicates that the magnitude of resistant Enterobacteriaceae within US hospitals is substantial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of the global spread of carbapenemaseproducing ECC isolates through patient transfer or colonized travelers in Europe, North America, the Far East and Australia has been well described in two reviews [2,3]. Recent meta-analysis and multicenter clinical study demonstrated a more than two-fold increased risk of mortality in patients infected with carbapenem-resistant gram-negative, MDR-positive bacteria, and a significant increase in healthcare cost [4,5]. It has been reported that mortality rate in the patients with CRE infections was as high as 44% [6].…”
Section: Introductionmentioning
confidence: 99%
“…the United States, with almost half of CRE infections consisting of carbapenemase producers (CP-CRE) (1)(2)(3). Patients hospitalized in the intensive care unit (ICU) setting are at particularly high risk of newly acquiring CRE during their hospital stay because the multiple preexisting medical conditions, compromised immune systems, lengthy unit stays, and significant rates of device and antibiotic utilization establish an ideal milieu for antibiotic resistance (4,5).…”
mentioning
confidence: 99%